2009
DOI: 10.1177/0748233709348394
|View full text |Cite
|
Sign up to set email alerts
|

Mold remediation in a hospital

Abstract: As occupants in a hospital, patients are susceptible to air contaminants that can include biological agents dispersed throughout the premise. An exposed patient can become ill and require medical intervention. A consideration for patients is that they may have become environmentally sensitive and require placement in an environment that does not compromise their health. Unfortunately, the hospital environment often contains more biological substances than can be expected in an office or home environment. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Occupational diseases from mold-related microbes is one of the most frequent categories documented for health care workers in the Finnish Registry of Occupational Diseases. Indoor air problems in hospital buildings have also been reported in other countries (Brownson, 1999(Brownson, , 2000Krajewska-Kulak et aI., 2007, 2009Nordstrom, Norback, & Akselsson, 1995;Nordstrom, Norback, & Wieslander, 1999).…”
Section: Applying Research To Practicementioning
confidence: 71%
See 1 more Smart Citation
“…Occupational diseases from mold-related microbes is one of the most frequent categories documented for health care workers in the Finnish Registry of Occupational Diseases. Indoor air problems in hospital buildings have also been reported in other countries (Brownson, 1999(Brownson, , 2000Krajewska-Kulak et aI., 2007, 2009Nordstrom, Norback, & Akselsson, 1995;Nordstrom, Norback, & Wieslander, 1999).…”
Section: Applying Research To Practicementioning
confidence: 71%
“…Due to functional changes and the ages of the premises, hospital buildings are under continuous repair. Several studies have shown that renovations of water-damaged buildings significantly contaminate the environment with microbes (Lee, 2009;Pini, Donato, Faggi, & Fanci, 2004).…”
mentioning
confidence: 99%
“…23 Other hospitals in the United States have also experienced unwanted mould issues; 24 while the research literature has reported on this topic and the legal implications for some time. 25,26 In Wuhan it is reported that there are 16 shelter hospitals and that some 'fever hospitals' are in sports arenas or exhibition center's due to the bed shortage at dedicated hospitals. The use of temporary shelters following natural disasters are known to affect people in a range of ways with obvious problems caused by crowding people at different stages of the infection cycle.…”
Section: Social Mediamentioning
confidence: 99%
“…3,4 Our survey highlighted the need for national education on environmental decontamination, mold remediation, and isolation unit operation after flooding, which deserves further evaluation in resource-limited settings. 5 Because Thailand had previously been affected by an outbreak of avian influenza and the 2009 H1N1 pandemic, the high response rates for several aspects of hospital disaster preparedness (eg, stockpiling of PPE and plans for surge capacity and operation of laboratory units) were not surprising. 6,7 Finally, our study emphasizes the role of a "safety culture" in a hospital as a strong predictor for HFP plans in this middle-income country.…”
Section: Hospital Flood Preparedness: a Survey Of 15 Provinces In Cenmentioning
confidence: 99%